Design, Synthesis, and Anticancer Activity Study of several New Schiff Base Imidyl Sulfa Drug Derivatives based on N-(Sulfamethoxazole-4-yl)-4-Aminomethylbenzylidene - Sura S. Raoof; Ahlam Marouf Al-Azzawi (Iraqi Journal of Pharmaceutical Sciences, 2026)
In this research, a series of new (Schiff base imidly sulfa drug) derivatives were designed and synthesized via many steps. In the first step, a sulfa drug (sulfamethoxazole) was chosen as a bioactive starting material and introduced in a condensation reaction with 4-amino acetophenone under microwave irradiation producing compound [1] N-(sulfamethoxazole-4\-yl)-4-amino methyl benzylidene. Subsequently, in the second step, compound [1] was introduced in reaction with three cyclic anhydrides, namely (succinic, maleic, and phthalic) anhydrides producing amic acid compounds [2-4], and these, inturn, introduced in the third step in a dehydration reaction via treatment with acetic anhydride and sodium acetate under reflux producing the target corresponding cyclic imide [5-7]. The work also involved a synthesis of other (Schiff base imidyl sulfa drug) derivatives (quinazoline) [8-10] via treatment of compounds [5-7] with anthranilic acid, while treatment of compound [5-7] with phthalic anhydride afforded other new derivatives (oxazepin) [11-13]. Since molecules of the newly synthesized compound contain three biologically active segments, two of them are sulfa drug and cyclic imide. At the same time, the third segment is Schiff base in compounds [5-7], quinazoline in compounds [8-10], and oxazepin in compounds [11-13]. They are expected to possess high biological activity. Thus, the work involved also studying the anticancer activity of the prepared compounds against breast cancer, and the results are promising.